Predictors of hepatocellular carcinoma in HCV cirrhotic patients treated with direct acting antivirals. Issue 2 (February 2019) - ,; Rendina, Maria; Ciancio, Alessia; Lampertico, Pietro; Brunetto, Maurizia R.; Di Marco, Vito; Zuin, Massimo; Andreone, Pietro; Villa, Erica; Troshina, Giulia; Degasperi, Elisabetta; Coco, Barbara; et al.
Abstract: Background: Despite the dramatic improvement in viral eradication rates that has been reached with direct antiviral agents (DAAs), the real benefit of viral eradication after DAAs on hepatocellular carcinoma (HCC) development is still controversial. Aim: To prospectively assess the risk of HCC occurrence and early recurrence in a large cohort of DAA-treated HCV-cirrhotic patients and to identify potential predictors of HCC development. Methods: We analyzed data prospectively collected from 1927 consecutive HCV-infected cirrhotic patients treated with DAA from January to December 2015 in 10 tertiary liver centers in Italy and followed-up for one year after therapy. 161 patients had a previous HCC. Results: 38/161 subjects developed tumor recurrence during the follow-up (recurrence rate = 24.8 per 100-year), patients with SVR had a significantly lower rate of recurrence. Lack of SVR and alpha-fetoprotein (AFP) were independent predictors of HCC recurrence. 50/1766 patients without a previous HCC history developed HCC during follow-up (incidence rate = 2.4 per 100-year). Lack of SVR was the strongest predictor of HCC development. Furthermore, patients with SVR and no stigmata of portal hypertension have a lower incidence rate of HCC (1.0 per 100-year). Conclusions: SVR is associated with a significant decrease of recurrent or de novo HCC. Baseline AFP and signs of portal hypertension can help to stratify the risk of HCC.